2012
DOI: 10.4161/cam.20167
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive guidance molecule A (RGMa)

Abstract: RGMa (repulsive guidance molecule a) was the first identified molecule that possessed the necessary functional activity to repulse and steer growth cones to their target in the brain. By binding to its neogenin receptor, RGMa caused the collapse of growth cones and encouraged axons to grow along specific trajectories in vitro. Although originally characterized in 1990, RGMa was not conclusively shown to mediate axon guidance in vivo for another 12 years. Loss-of-function analysis in mice revealed that RGMa may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Both DMRs, containing different sets of CpG sites, were located at a CpG island, one situated at a promoter, the other at an intron, and showed hypomethylation for both associations, which could be indicative of a transcriptional upregulation. In addition, we identified DMRs annotated to RGMA , which has an important role in neurological development and operates through axon guidance and programmed apoptosis in the developing embryonic neural tube (Matsunaga et al, 2004; Key and Lah, 2012). RGMA is associated with the selective degeneration of dopaminergic neurons in the substantia nigra in a Parkinson’s disease model in mice (Korecka et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Both DMRs, containing different sets of CpG sites, were located at a CpG island, one situated at a promoter, the other at an intron, and showed hypomethylation for both associations, which could be indicative of a transcriptional upregulation. In addition, we identified DMRs annotated to RGMA , which has an important role in neurological development and operates through axon guidance and programmed apoptosis in the developing embryonic neural tube (Matsunaga et al, 2004; Key and Lah, 2012). RGMA is associated with the selective degeneration of dopaminergic neurons in the substantia nigra in a Parkinson’s disease model in mice (Korecka et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One such guidance protein, repulsive guidance molecule-A (RGM-A), a glycosylphosphatidylinositol (GPI)-linked membrane glycoprotein, mediates chemorepulsive signals to steer axonal growth cones to their targets in the brain 2,3 . Studies have shown notable guidance roles for RGM-A and its receptor neogenin during embryonic development and morphogenetic processes including cell adhesion, cell migration, cell polarity and cell differentiation 4,5 . Recent evidence identified RGM-A in peripheral tissues, where it was shown to play crucial roles in the onset of an acute inflammatory response and in the pathology of autoimmune encephalomyelitis 68 .…”
Section: Introductionmentioning
confidence: 99%
“…The repulsive guidance molecule a(RGMa) has been demonstrated to impede neurite outgrowth in postnatal cerebellar neurons (16,17). In rats, the induction of RGMa expression following spinal cord injury at the site of the lesion has been observed (18). Neutralization of RGMa with local administration of an antibody was identified to significantly facilitate axon regeneration following spinal cord injury (15,19).…”
Section: Introductionmentioning
confidence: 99%
“…Neutralization of RGMa with local administration of an antibody was identified to significantly facilitate axon regeneration following spinal cord injury (15,19). In addition, RGMa has been indicated to participate in the development of scar tissue following injury and in the myelination of fiber tracts (18). Furthermore, RGMa has been indicated to be one of the most potent inhibitors of axonal growth (17).…”
Section: Introductionmentioning
confidence: 99%